Sustainable soil and land management: a systems-oriented overview of scientific literature - Mason, Eloïse; Bispo, Antonio; Matt, Mireille; Helming, Katharina; Rodriguez, Elena; Lansac, Rocio; Carrasco, Violeta; Hashar, Mohammad Rafiul; Verdonk, Loes; Prokop, Gundula; Wall, David; Francis, Nancy; et al. (Frontiers in Soil Science, 2023)
Healthy soil is vital for our wellbeing and wealth. However, increasing demand for food and biomass may lead to, as well as unsustainable soil and land management practices or soil sealing are that threatening soils globally. Other degradation processes such as soil sealing also endanger soil resources. Identifying and accessing the best available knowledge is crucial to address related sustainability issues and promote the needed transition towards sustainable soil and land management practices. Such knowledge has to cover all knowledge domains, system knowledge, target knowledge, and transformation knowledge. However, a comprehensive overview of existing research addressing societal needs related to soil is still missing, which hinders the identification of knowledge gaps. This study provides a detailed analysis of scientific literature to identify ongoing research activities and trends. We conducted aA quantitative and qualitative analysis of scientific literature related to sustainable soil and land management was conducted. Ausing a systems-oriented analytical framework was used that combines soil and land related societal challenges with related knowledge domains was conducted. Our analysis revealed a significant increase in scientific publications activities and related interest in soil and land use-related research, above the average increase of publications within all scientific fields. Different forms of reduction and remediation of soil degradation processes (e.g. erosion, contamination) have been studied most extensively (e.g. erosion, contamination)., while oOther topic areas like land take mitigation, soil biodiversity increase, increase of provision of ecosystem services provisionincrease and climate change mitigation and adaption seem to be rather recent concerns, less investigated. We could highlight the importance of context-specific research, as different regions require different practices. Especially For instance, boreal, tropical, karst and peatland regions were less studiedrequire more attention. Furthermore, we found that diversifying soil management practices such as agroforestry or including livestock into arable systems are valuable options for increasing biomass, mitigating/adapting to climate change, and improving soil related ecosystem services. A recent trend towards the latter research topic indicates the transition from a soil conservation-oriented perspective to a soil service-oriented perspective, which may be better suited to integrate the socio-economic dimensions of soil health improvement alongside the ecological dimension.